John Company's Last War - English, Barbara, (Brill | Manohar Publishers & Distributors, 2024)
In the nineteenth century, the British crown expanded its reach in almost all parts of the world from China to America, overpowering the Portuguese, Spanish, Dutch, and the French. The period also witnessed the contestation between the English East India Company, the Czarist Russia, and the Qajar Persian kingdom to prevent Russian expansion into India by creating a buffer zone in Central Asia along with the support of the Emirate of Afghanistan. The English East India Company's feud with the Persians in 1856, also known as the Anglo-Persian war, forms the basis of this monograph. This book contains descriptions taken from memoirs, journals, letters, and correspondences from lower and upper officials, military men, and the Governor-General. It also focuses on the exploits of the Victorian military and the arrival of the British in cities, such as Kabul, Herat, and Tehran.